2014
DOI: 10.3748/wjg.v20.i33.11808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medical therapy on patients with Crohn’s disease requiring surgical resection

Abstract: AIM:To evaluate the impact of medical therapy on Crohn's disease patients undergoing their first surgical resection. METHODS:We retrospectively evaluated all patients with Crohn's disease undergoing their first surgical resection between years 1995 to 2000 and 2005 to 2010 at a tertiary academic hospital (St. Paul's Hospital, Vancouver, Canada). Patients were identified from hospital administrative database using the International Classification of Diseases 9 codes. Patients' hospital and available outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…significantly increased rates of small bowel fistula repair, postoperative infections and anastomotic related complications . The proportion of patients with perforating disease (27.3%) in the present study is relatively low compared to the 43.9% perforating disease reported in a meta‐analysis . In addition, there was no significant difference in the number of fistulas between the groups with and without anti‐TNF, suggesting that the threshold for the gastroenterologist to refer the patient to the surgeon is relatively low with adequate discussion of patients in a multidisciplinary team.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…significantly increased rates of small bowel fistula repair, postoperative infections and anastomotic related complications . The proportion of patients with perforating disease (27.3%) in the present study is relatively low compared to the 43.9% perforating disease reported in a meta‐analysis . In addition, there was no significant difference in the number of fistulas between the groups with and without anti‐TNF, suggesting that the threshold for the gastroenterologist to refer the patient to the surgeon is relatively low with adequate discussion of patients in a multidisciplinary team.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, no reduction in length of inflammation in clinical nonresponders was observed (decrease from 15.6 to 15.6 cm, P = 0.98) [7]. In the previously mentioned study by Fu et al, no significant difference in the length of resected small bowel was found in patients treated with anti-TNF vs patients without anti-TNF (mean 23.0 vs 21.5 cm, P = 0.92) [6].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Given that no specific anti‐fibrotic therapy exists, these patients are often initially treated with the best available medical anti‐inflammatory therapy. Strikingly, despite the revolutionary emergence of biologic agents over the past two decades, estimates for surgical resection of fibrostenotic disease either remain unchanged, 4 or have shifted from less emergent to more elective procedures 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is difficult for Korean patients in an earlier phase of CD to obtain infliximab, a factor that might interfere with the ability to demonstrate an association between infliximab use and better treatment results. In fact, another study failed to demonstrate a reduction in the reoperation rate following the use of anti-TNF-α antibodies and indicated a need for earlier infliximab treatment [ 26 ]. Additional studies have suggested that top-down therapy might be more effective than conventional management for patients in remission [ 27 28 ], although the effect of top-down therapy on the CD reoperation rate is not yet well established.…”
Section: Discussionmentioning
confidence: 99%